General practitioner notes as a source of information for case-control studies in young women. UK National Case-Control Study Group. Issue 1 (February 1994) - Chilvers, C E; Pike, M C; Taylor, C N; Hermon, C; Crossley, B; Smith, S J
Abstract : STUDY OBJECTIVE–The UK National Case-Control Study was carried out to investigate the relationship between oral contraceptive use and breast cancer risk. This study investigates whether general practitioner notes could be used as the sole data source for epidemiological studies of young women and what the effect would be on non-response and recall bias. DESIGN–Case-control study with data on gynaecological, obstetric, and contraceptive history collected at interview and from general practitioners' notes. Information from these two sources was compared. SETTING–This was a population-based study. PARTICIPANTS–Altogether 755 women with breast cancer aged under 36 years at diagnosis, each with an age-matched control, participated in the study. Response rates at interview were 72% and 89% for cases and controls but GP data were available for 90% of the 1049 case and first-selected control pairs. MAIN RESULTS–There was generally good agreement between the two data sources with respect to obstetric history and gynaecological procedures (hysterectomy, oophorectomy, and tubal ligation). The use of intra-uterine devices, or diaphragm, and partner's vasectomy were not reliably recorded in the GP's notes. The overall results of the UK study would have been qualitatively the same with respect to the relationship between oral contraceptive use and breast cancer risk if GP notes only had been used, in spite of the fact that only about half of all oral contraceptive usage was recorded in the notes. Response rates would have been higher, recall bias eliminated, and the cost of the study halved. CONCLUSIONS–When planning case-control studies in young women, the possibility of using GP notes as the primary data source should be considered. Lack of data on potential confounding factors is a possible drawback to such use. The practice of destroying GP's notes shortly after the death of patients seriously restricts the possibility of using these notes when studying rapidly fatal conditions.